The protein kinase R modifies gut physiology to limit colitis - Yim, Howard Chi Ho; Chakrabarti, Arindam; Kessler, Sean; Morimoto, Hiroyuki; Wang, Die; Sooraj, Dhanya; Ahmed, Afsar U.; de la Motte, Carol; Silverman, Robert H.; Williams, Bryan RG.; Sadler, Anthony J. (Frontiers in Immunology, 2023)
Here we investigate the function of the innate immune protein kinase R (PKR) in inflammatory bowel disease. To model a colitogenic role of PKR we determine the physiological response to dextran sulfate sodium (DSS) of wild type and two transgenic mice mutated to express either a kinase-dead PKR or to ablate expression of the kinase. These experiments recognise kinase dependent and independent protection from DSS induced weight loss and inflammation, against a kinase-dependent increase in the susceptibility to DSS induced injury. We propose these effects arise through PKR dependent alteration of gut physiology, evidenced as altered goblet cell function and changes to the gut microbiota at homeostasis and suppression of inflammasome activity. These findings establish that PKR plays a role as both a protein kinase and a signalling molecule in instituting immune homeostasis in the gut.